2022
DOI: 10.23950/jcmk/12720
|View full text |Cite
|
Sign up to set email alerts
|

Effect of women’s health literacy levels on their beliefs about breast cancer screening

Abstract: <b>Objective:</b> This study was conducted to examine the effect of women's health literacy level on breast cancer screening beliefs.<br /> <b>Material and methods:</b> This study has been done descriptively. In data collection, measurement tools such as 'Descriptive Information Form', 'Health Literacy Scale' and 'Breast Cancer Screening Beliefs Scale' developed based on literature and observations were used. Statistical analysis of the data was made in SPSS 20.0 statistical packa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Young patients have a higher mortality rate than older patients, even among those with early-stage breast cancer ( 21 ). Young patients are also more susceptible to treatment-related adverse effects and cancer-related psychosocial problems.…”
Section: Discussionmentioning
confidence: 99%
“…Young patients have a higher mortality rate than older patients, even among those with early-stage breast cancer ( 21 ). Young patients are also more susceptible to treatment-related adverse effects and cancer-related psychosocial problems.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in Turkey higher HL levels were observed among women who had prior exposure to information regarding Breast Self-Exams, Clinical Breast Exams, mammography, and mammary ultrasonography. Notably, improved HL in women corresponded to an enhanced interest in seeking out screening techniques crucial for the early identification of breast cancer [77].…”
Section: Improving Health Literacy: a Multifaceted Approachmentioning
confidence: 99%